Use of Crumb Rubber Modified Binders and Asphalt Mixtures in Public Works Authority Road Projects - State of Qatar - Santagata, Ezio; Sebaaly, Haissam; Idris, Osman Elhusain Mohamed; Ali, Moaaz Hashim M. M.; Al-Emadi, Khalid Mohd I (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper illustrates the approach adopted by the Public Works Authority (Ashghal) of the State of Qatar for the widespread implementation in road projects of paving technologies related to the use of crumb rubber modified binders (CRMBs). Such an approach has entailed the monitoring of a full-scale preliminary trial, the definition of a prequalification system for crumb rubber and CRMB producers, and the development of mix design and quality control guidelines applicable to CRMB asphalt mixtures. Experimental results obtained in the preparatory phases of work and during the approval process of materials and mixtures are critically presented.